Evaluasi Analisis “SWOT” Pembinaan Prestasi Olahraga Petanque di Kabupaten Tulungagung - Derbiansyah Farid Varrahman (Pusat Riset dan Inovasi Nasional, 2024)
Maximum achievement in sports is the main goal that must be achieved by all athletes, both individually and collectively. Producing peak performance requires scheduled and targeted coaching. Based on this, researchers conducted this research to determine the context, input, process and product for assessing the development of Petanque sports achievements in the Tulungagung area. The research method uses non-experimental methods with qualitative descriptive analysis. From the data sources obtained, this research method is document analysis. The research results show that the development of iron sports achievements has several advantages because this sport is increasingly popular and has received support from the government and society. However, there are also weaknesses in limited infrastructure and lack of funds to develop achievements. Apart from that, a number of opportunities have been identified, such as increasing public interest in the sport of snooker and the potential to produce outstanding athletes at international level. However, there are also threats, such as intense competition from other ancient sports. It was concluded that the achievements of the sport of petanque in Tulungagung were supported by athletes who excelled but did not receive adequate support.